Precio del petróleo en Colombia: impacto en la inflación y el desempleo (1987-2015). (2016)
The paper examines the effects of the international oil price, specifically the WTI, on the Colombian economy. The work uses a theoretical framework implemented by Blanchard and Galí (2005) where empirical evidence is made that the price of oil can influence the behavior of macroeconomic variables; this model is called the "new standard Neo-Keynesian model" and explains the transmission channels of the oil price in the country's economy. By estimating an SVAR model of reduced form and applying bivariate regressions, it found that the price of oil over time had different impacts, however, in recent years as a consequence of the fall in the price of crude oil in inflation has been low. On the other hand, it was found that employment has not affected significantly by the variation in the price of petroleum since there is no causality among the variables.